VD_FINDINFO Décision / 2012 / 1008 vom 12. Juni 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ | 221 al. 1 let. c CPP (CH), 221 CPP (CH), 227 al. 7 CPP (CH)